Implementation of the Rapid Application Development (RAD) Model in the Web-Based MSME Product Sales System - Riski Dwi Anjani; Ariansyah; Phinton Panglipur (Yayasan Kita Menulis, 2026)
A web-based sales system is an effective solution to help micro, small, and medium enterprises (UMKM) manage sales efficiently and in a structured manner. This research was conducted at Anisa Store, one of the UMKM in Majasari Village, Prabumulih, which still uses a manual sales process, so it has difficulty in recording data. The purpose of this study is to build a web -based sales system using the Rapid Application Development (RAD) Model, which allows the system development process to be carried out quickly and actively involves users. The RAD model consists of several stages, namely needs planning, design, construction and relocation. The result of this study is a web-based sales system that can be used by the owner of Anisa Store to manage product data, sales transactions, and shipping. By implementing this system, it is expected to increase the marketing reach of Anisa Store.